2012
DOI: 10.1021/jp305510c
|View full text |Cite
|
Sign up to set email alerts
|

Why Is the Oxidation State of Iron Crucial for the Activity of Heme-Dependent Aldoxime Dehydratase? A QM/MM Study

Abstract: Aldoxime dehydratase is a heme-containing enzyme that utilizes the ferrous rather than the ferric ion to catalyze the synthesis of nitriles by dehydration of the substrate. We report a theoretical study of this enzyme aimed at elucidating its catalytic mechanism and understanding this oxidation state preference (Fe 2+ versus Fe 3+ ). The uncatalyzed dehydration reaction was modeled by including three and four water molecules to assist in the proton transfer, but the computed barriers were very high at both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…However, this high level of KE activity was somehow lost during purification by metal‐affinity chromatography and after storage at 4 °C (Figure S5). Because the natural aldoxime dehydratase activity of Oxd is associated with the ferrous state of its heme iron (differences in coordination modes between ferric/ferrous iron and aldoxime), we assumed that the Kemp substrate binds to the heme iron of Oxd in a similar manner to that of the natural substrate during catalysis. Thus, the observed deterioration in KE activity might be related to the change in the oxidation state of heme iron (i.e., from ferrous to ferric) during purification and storage.…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, this high level of KE activity was somehow lost during purification by metal‐affinity chromatography and after storage at 4 °C (Figure S5). Because the natural aldoxime dehydratase activity of Oxd is associated with the ferrous state of its heme iron (differences in coordination modes between ferric/ferrous iron and aldoxime), we assumed that the Kemp substrate binds to the heme iron of Oxd in a similar manner to that of the natural substrate during catalysis. Thus, the observed deterioration in KE activity might be related to the change in the oxidation state of heme iron (i.e., from ferrous to ferric) during purification and storage.…”
Section: Methodsmentioning
confidence: 53%
“…The heme‐containing enzyme aldoxime dehydratase (Oxd) is part of the aldoxime‐nitrile pathway in various microorganisms, where it catalyzes the dehydration of an aliphatic or aryl‐aldoxime ( 3 ) to the corresponding nitrile ( 4 ; Scheme B) . Oxd‐catalyzed dehydration of aldoxime starts with the heme iron in its ferrous state, and involves the direct approach of substrate to the heme iron and deprotonation of the β‐hydrogen of aldoxime by a distal histidine . Because of the similarity in the reaction mechanisms of Kemp elimination and aldoxime dehydration and in the chemical structure of their substrates (Scheme ), we investigated whether Oxd could use its distal histidine as a catalytic base and its heme environment to stabilize the transition state of the deprotonation of 1 , thus catalyzing Kemp elimination.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the system setup are documented in the Supporting Information of our previous article and will thus not be repeated here. The QM/MM optimized structures from our previous study (BS100, QM region M3a , 157 atoms) were subjected to charge deletion analysis . On the basis of this analysis, important active‐site residues and water molecules with electrostatic effects of more than 2 kcal/mol were incorporated into the QM region, which was thus extended to 408 atoms with a total charge of −5 (QM region M4 , see Int1 in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the choice of the QM region is crucial for the proper description of the reaction pathway. A charge deletion analysis was found to be useful to identify those residues that have significant electrostatic effects on the reaction energetics and that should, therefore, be included when designing larger QM regions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on earlier studies, which identified intermediates in the catalytic cycle of aldoxime dehyratases through resonance Raman spectroscopic analysis, FTIR spectroscopy and quantum mechanics/molecular mechanics (QM/MM) calculations,, and all above‐mentioned mutations to identify the crucial amino acid residues, the mechanism for OxdA (and in analogy for all other Oxds) was proposed to proceed as follows (Scheme ). First, the aldoxime enters the active site and is coordinated through its N atom to the Fe II atom of heme b. Hydrogen bonds between the OH group of the aldoxime and the serine and distal histidine residue increase fixation of the substrate.…”
Section: Properties Structures and Mechanism Of Oxdsmentioning
confidence: 99%